# Relativistic beaming/ Aberration effect derivation

I'm researching applications of relativistic beaming and I want to derive a formula for the aberration effect but I am stuck (I am off by a factor of 1/c). Here's what I have:

Consider a star in its rest frame, $$S^\prime$$, moving at speed $$v$$ that emits a photon at an angle $$\theta^\prime$$. In the $$S$$ frame, the observer measures the angle to be $$\theta$$. I made a picture below to illustrate this We have from the picture the identities $$\cos(\theta)=\frac{x}{ct}$$ and $$\cos(\theta^\prime)=\frac{x^\prime}{ct^\prime}$$. The Lorentz transformations are from the prime coordinate system are the following:

$$x^\prime=\frac{x-vt}{\sqrt(1-\beta^2)}=t\frac{\cos(\theta) -\beta}{\sqrt(1-\beta^2)}$$

$$y^\prime =y$$

$$t^\prime=\frac{t-\frac{vx}{c^2}}{\sqrt(1-\beta^2)}=t\frac{1-\beta\cos(\theta)}{\sqrt(1-\beta^2)}$$

Now, $$\cos(\theta^\prime)=\frac{x^\prime}{ct^\prime}=\frac{t\frac{\cos(\theta) -\beta}{\sqrt(1-\beta^2)}}{ct\frac{1-\beta\cos(\theta)}{\sqrt(1-\beta^2)}}$$

After simplifying we get $$\cos(\theta^\prime)=1/c \frac{\cos(\theta)-\beta}{1-\beta\cos(\theta)}$$

Which is almost the relativistic aberration formula but again I am off by $$c^{-1}$$. Does anyone know what is wrong with this derivation?

• I guess they will close this question as off topic and my answer will be deleted too, so just in case, the answer is you have missed a $c$ in your very first question $x=ctcos\theta$. – Paradoxy Jul 26 '19 at 1:59
• Why is this considered off topic? – hwhorf Jul 26 '19 at 14:31
• It's not considered as off-topic yet, I'm just guessing it will be. Because although you have shown some effort in solving your question, "you are not asking about a physical concept" and "giving the full solution to question like this is also forbidden", several answers of mine were deleted like this. So always check your topic before they close it. – Paradoxy Jul 26 '19 at 15:21

$$\cos(\theta)=\frac{x}{ct}\rightarrow x=ct\cos(\theta)$$ $$c\beta=v$$ $$x'=\frac{x-vt}{\sqrt{1-\beta^2}}=\frac{ct \cos(\theta)-c\beta t}{\sqrt{1-\beta^2}}=ct(\frac{ \cos(\theta)-\beta }{\sqrt{1-\beta^2}})$$